AITPO (ANTECEDENT, INPUT, TRANSACTION, PRODUCT, OUTCOMES): MIXED MODEL EVALUASI CIPP DAN COUNTENACE SEBAGAI PENDEKATAN EVALUASI PROGRAM KAMPUS MENGAJAR - Yoga Budi Bhakti; Burhanuddin Tola; Dinny Devi Triana (Yayasan Hurriah, Banda Aceh, 2022)
English: Kampus Mengajar is a teaching assistance activity at the level of educational units and part of the Merdeka Campus Program. The purpose of the Kampus Mengajar program is for students to have competence and provide an off-campus learning experience. In addition to having a good purpose, the Kampus Mengajar Program saves many problems faced by colleges and schools. This research is a form of literary study to develop the AITPO evaluation model (Antecedent, Input, Trasaction, Product, Outcomes) which is a combination of CIPP and Countenance models. The combination of CIPP and Countenance evaluation models is considered as a complementary approach in the implementation of evaluation of the Kampus Mengajar Program. Based on the results of the study it can be concluded that the mixed of the two models is projected to provide a thorough and in-depth evaluation of the implementation of the Kampus Mengajar program. With the evaluation of this AITPO model can also be obtained comprehensive recommendations and complement each other in the continuity of the program. Bahasa: Kampus Mengajar merupakan kegiatan asistensi mengajar di tingkat satuan pendidikan serta bagian dari Program Kampus Merdeka. Tujuan program Kampus Mengajar agar mahasiswa memiliki kompetensi serta memberikan pengalaman belajar di luar kampus. Disamping memiliki tujuan yang baik, Program Kampus Mengajar menyimpan banyak masalah yang dihadapi oleh Perguruan Tinggi maupun Sekolah. Penelitian ini merupakan bentuk kajian literaktur untuk mengembangkan model evaluasi AITPO (Antecedent, Input, Trasaction, Product, Outcomes) yang merupakan gabungan antara model CIPP dan Countenance. Penggabungan model evaluasi CIPP dan Countenance dinilai sebagai pendekatan yang komplementer dalam pelaksanaan evaluasi terhadap Program Kampus Mengajar. Berdasarkan hasil penelitian dapat disimpulkan bahwa penggabungan kedua model tersebut diproyeksikan dapat membeikan evaluasi secara menyeluruh dan mendalam tentang pelaksanaan program Kampus Mengajar. Dengan evaluasi model AITPO ini juga dapat didapatkan rekomendasi secara komprehensif dan saling melengkapi dalam kelangsungan program.